2016
DOI: 10.31055/1851.2372.v51.n2.14847
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciación cromosómica en tres especies de Leptostemonum (Solanum, Solanaceae) endémicos de islas oceánicas.

Abstract: Diferenciación cromosómica en tres especies de Leptostemonum (Solanum, Solanaceae) endémicos de islas oceánicas. Los cromosomas de Solanum nelsonii, S. sandwicense (endémicosde las islas Hawaii) y de S. vespertilio (de las islas Canarias) fueron estudiados por medio de tinción clásica, bandeo CMA/DAPI y FISH con sondas para los genes de ADNr de 18-5.8-26S y 5S. El objetivofue comprobar cambios cromosómicos (número cromosómico, cariotipo, patrones de heterocromatina y loci de ADNr) durante la evolución de estos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Different authors have reported that euploidy is frequent in oceanic islands and has been associated with the recent origin and narrow geographical range of oceanic island species (Weiss-Schneeweiss et al 2007;Mandáková et al 2010;Chiarini and Gauthier 2016;), but euploidy seems to be the rule in recent angiosperm speciation (Ehrendorfer 1970, Otto and Whitton 2000, Wood et al 2009. Our results disagree with the association between euploidy and recent origin of species since we found that euploidy was more frequent in the common species and the Atlantic forest total and exclusive species, which are considered older than Caatinga and Cerrado species (e. g. Graham 2011).…”
Section: Table 1)mentioning
confidence: 99%
“…Different authors have reported that euploidy is frequent in oceanic islands and has been associated with the recent origin and narrow geographical range of oceanic island species (Weiss-Schneeweiss et al 2007;Mandáková et al 2010;Chiarini and Gauthier 2016;), but euploidy seems to be the rule in recent angiosperm speciation (Ehrendorfer 1970, Otto and Whitton 2000, Wood et al 2009. Our results disagree with the association between euploidy and recent origin of species since we found that euploidy was more frequent in the common species and the Atlantic forest total and exclusive species, which are considered older than Caatinga and Cerrado species (e. g. Graham 2011).…”
Section: Table 1)mentioning
confidence: 99%